Ex-vivo perfusion of donor hearts for human heart transplantation (PROCEED II): a prospective, open-label, multicentre, randomised non-inferiority trial. Issue 9987 (27th June 2015) - Ardehali, Abbas; Esmailian, Fardad; Deng, Mario; Soltesz, Edward; Hsich, Eileen; Naka, Yoshifumi; Mancini, Donna; Camacho, Margarita; Zucker, Mark; Leprince, Pascal; Padera, Robert; Kobashigawa, Jon; et al.
Summary: Background: The Organ Care System is the only clinical platform for ex-vivo perfusion of human donor hearts. The system preserves the donor heart in a warm beating state during transport from the donor hospital to the recipient hospital. We aimed to assess the clinical outcomes of the Organ Care System compared with standard cold storage of human donor hearts for transplantation. Methods: We did this prospective, open-label, multicentre, randomised non-inferiority trial at ten heart-transplant centres in the USA and Europe. Eligible heart-transplant candidates (aged >18 years) were randomly assigned (1:1) to receive donor hearts preserved with either the Organ Care System or standard cold storage. Participants, investigators, and medical staff were not masked to group assignment. The primary endpoint was 30 day patient and graft survival, with a 10% non-inferiority margin. We did analyses in the intention-to-treat, as-treated, and per-protocol populations. This trial is registered with ClinicalTrials.gov, number NCT00855712 . Findings: Between June 29, 2010, and Sept 16, 2013, we randomly assigned 130 patients to the Organ Care System group (n=67) or the standard cold storage group (n=63). 30 day patient and graft survival rates were 94% (n=63) in the Organ Care System group and 97% (n=61) in the standard cold storage group (difference 2·8%, one-sided 95% upper confidence bound 8·8; p=0·45). Eight (13%) patients in the Organ Care System group and nine (14%) patients in the standard cold storage group had cardiac-related serious adverse events. Interpretation: Heart transplantation using donor hearts adequately preserved with the Organ Care System or with standard cold storage yield similar short-term clinical outcomes. The metabolic assessment capability of the Organ Care System needs further study. Funding: TransMedics.